THE MARKETING MIX FOR LOW COST HEALTHCARE - George, Julie; Shah, Manita D. (International Journal of Research -GRANTHAALAYAH, 2017)
The Indian health care industry has a history of dealing with poor doctor-patient ratio, shortage of medical professionals, poor health infrastructure, and low expenditure on healthcare information technology; steep out of pocket spending (OOP), low health insurance coverage, inadequate government spending, poor access to health care facilities and social stigma related to diseases. The unique mindset and ability for frugality has successfully been applied in offering low cost healthcare of uncompromised quality. While this has been achieved by few innovative entrepreneurs, it is imperative to help the new entrants with the collective experience in dealing with the rural market. A qualitative study was undertaken. Five Indian organizations, that have earned accolades and awards for successfully innovating for the poor were studied in-depth. The research looked into the challenges faced by the entrepreneurs. The methods and measures that evolved from their operation were analyzed. In order to help marketers learn from the pioneers, the paper has simplified the measures and steps in marketing to the familiar P’s of the marketing mix. In healthcare, the product is tied with service and the need is to work on all the 7P’s is useful. Keywords: frugal, innovation, entrepreneurship, marketing mix, healthcare.